The Role of Buzz and Viral Marketing on SMEs Online Shop Marketing Performance: CB-SEM AMOS Analysis - Purwanto, Agus; Sulaiman, Anwar; Fahmi, Khaerul (International Journal of Social and Management Studies, 2023)
The purpose of this research is to analyze the relationship between buzz marketing and SMEs marketing, the relationship between viral marketing and SMEs marketing performance and the relationship between buzz marketing and viral marketing. This research method is quantitative. The data collection technique in this study used an online questionnaire technique which was designed using a Likert scale of 1 to 7 and distributed to 650 SMEs consumers who were selected by simple random sampling method. This data processing tool uses Structural Equation Modeling (SEM) using the AMOS (Analysis of Moment Structure) program version 26. Prior to data analysis, validity and reliability tests of the questionnaire used are first performed. To measure its validity, the score of each question item was used which was correlated with the total item score in one variable. After testing the validity and reliability, then performed data analysis. Data analysis and interpretation are carried out to answer the problems that have been formulated and answer the hypotheses. In this study, data analysis used Structural Equation Modeling (SEM) with AMOS software. The results of this study are that buzz marketing has a positive and significant effect on SMEs marketing performance. Viral marketing has a positive and significant effect on SMEs marketing performance. Buzz marketing has a positive and significant effect on Viral marketing